loga(x-5)-loga(x+9)=loga(x-7)-loga(x+9)

all the a's are lower

1. log [(x-5)/(x+9)]= log[(x-7)/(x+9) ]

(x-5)(x+9) = (x-7)(x+9)

x-5 = x- 7
no solution

posted by Damon
2. x-5/x+9 is equal to x-7/x+9

(x+9 )(x-5) is equal to (x-7)(x+9)
x2-5x+9x -40 equals x2-9x-7x-63
nw solve from there:)

posted by arlana shakur

## Similar Questions

1. ### math/calculus

solve the equation loga(x-5)- loga (x+9)=loga(x-7)-loga(x+9) all a's are lower please show work
2. ### Algebra help

If loga 8=2.079, loga 5=1.609, and loga 3=1.099, find the following? 19.) loga 8/3 is this 1.89? 20.) loga 24 Not sure 21.) loga 25 not sure how to do this
3. ### math trouble

I have 2 problems I need help with using either substitution or elimination method what is the solution set of 3x -2y = -4 and 5x = 2y? Second, Given: log sub a 2 = .4, log sub a 3 = .5, log sub a 5 = .8 what is the value of log
4. ### HELP!

I have no idea what the answer to this problem is, I'm given choices but I'm still lost. Given: log sub a 2=.4, log sub a 3 =.5, log sub a 5=.8 what is log sub a .01? a)0.7 b)-0.6 c)1.44 d)-2.4 Please Help! loga 10 = loga2 +loga5
5. ### Math Algebra 2

#4. Express the logarithm in terms of log2M and log2N: log2 1/MN #5. Simplify: log4 3 - log4 48 #6. Solve the equation: loga x = 3/2loga 9 + loga 2 #7. Solve the equation: logb (x2 + 7) = 2/3logb 64 #8. Solve the equation: loga
6. ### Math - Properties of Logarithm

Can someone show how to this question. Loga(x+3) + Loga(x-3) = 3 I don't know if I'm typing this correctly the a is the base. So, I'm thinking, Loga((x+3)(x-3)) = 3 (x+3)(x-3) = 3^a x^2 - 9 = 3^a, x^2 = 3^a + 9 x = sqrt(3^a + 9)
7. ### Math

Solve the logarithmic equation. Please show all of your work. Loga(x+4) + loga(x-4) = 4
8. ### Math

Which of the following is not a property of logarithms? A. log(A - B) = logA/logB B. logA + logB = logAB C. xloga = loga^x D. log(b) b^x = x
9. ### algebra

express as an equivalant expression that is a single logarithmic and simplfy if poissible loga(2x+10)-loga(x^2-25)
10. ### Algebra

1. Solve log(4/x) (x^2 - 6) = 2. (note: the (4/x) is underscored) 2. Show that loga [(x + {sqrtx^2-5}) / 5] = -loga (x - (sqrtx^2-5))

More Similar Questions